On the localization of quasi–Lamb waves in the layer of ideal fluid — elastic layer system - Bahno, O. M. (Reports of the National Academy of Sciences of Ukraine, 2016)
Basing on the three–dimensional linear equations of the classical theory of elasticity for a solid and the linearized Euler equations for a fluid, the propagation of quasi–Lamb waves in the layer of ideal compressible fluid — elastic layer system is studied. For the normal waves, the dispersion curves are constructed in a wide range of frequencies. The effect of thickness of the fluid layer on the dispersion of phase velocities of quasi–Lamb modes in a hydroelastic waveguide is analyzed. The localization properties of the lower quasi–Lamb modes in elastic–fluid waveguides are studied.